KONTRIBUSI AGROFORESTRI TERHADAP KETAHANAN PANGAN RUMAH TANGGA PETANI DI DESA NGARIP KECAMATAN ULU BELU KABUPATEN TANGGAMUS - Susni Herwanti (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2016)
Agroforestry is a land use systems that are considered able to provide economic benefits, ecological and social, including in the village of Ngarip. This study seeks to prove the ability of agroforestry economy, especially in providing food for households. The purpose of this study is to identify agroforestry plants, analysis of food security of agroforestry and determine the level of food security of farmers agroforestry. Samples taken in this research is 93 respondents. Data collected in the form of primary data and secondary data. The data were analyzed descriptively qualitative. The results showed that there are 40 species of plants that exist in agroforestry, which consists of vegetables, fruits, tubers, grains, woody plants, rattan, bamboo and grass. Based on the analysis of food availability, food is available in the peasant households consisting of vegetables, fruits and grains. The study found that households Ngarip Village farmers have sufficient levels of food security with a score of 12.3.